2004
DOI: 10.1037/0021-9010.89.1.3
|View full text |Cite
|
Sign up to set email alerts
|

Risk Propensity Differences Between Managers and Entrepreneurs and Between Low- and High-Growth Entrepreneurs: A Reply in a More Conservative Vein.

Abstract: A recent article (W. H. Stewart & P. L. Roth, 2001) in the Journal of Applied Psychology presented the conclusion from meta-analysis that entrepreneurs have a higher risk propensity than managers and that this propensity is particularly pronounced among the growth-oriented. A previously unresolved question was said to be laid to rest and a "vital component" of a theory of entrepreneurship established. The present article disagrees and cites data from 14 studies not included in the Stewart and Roth (2001) analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
187
1
6

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(205 citation statements)
references
References 44 publications
7
187
1
6
Order By: Relevance
“…Researchers have historically assumed that entrepreneurs are more willing to bear risk than traditional wage earners (Knight 1921;McClelland 1961). However, empirical evidence has shown that, on average, there is little difference in risk profiles between these two categories of individuals (e.g., Brockhaus 1980;Miner and Raju 2004). This suggests that entrepreneurs are not necessarily a breed apart, and instead share the same variance in propensity toward accepting and bearing risk that all people do (Evans and Leighton 1989;Macko and Tyszka 2009).…”
Section: Moderating Role Of Risk Propensitymentioning
confidence: 92%
“…Researchers have historically assumed that entrepreneurs are more willing to bear risk than traditional wage earners (Knight 1921;McClelland 1961). However, empirical evidence has shown that, on average, there is little difference in risk profiles between these two categories of individuals (e.g., Brockhaus 1980;Miner and Raju 2004). This suggests that entrepreneurs are not necessarily a breed apart, and instead share the same variance in propensity toward accepting and bearing risk that all people do (Evans and Leighton 1989;Macko and Tyszka 2009).…”
Section: Moderating Role Of Risk Propensitymentioning
confidence: 92%
“…The variable capturing financing constraints is constrained i,p , which is equal to one if firm i declares financing constraints (14%), and zero otherwise. 13 The other control variables are size i,p , which is the number of employees of firm i, and age i,p , which is the age of firm i (relative 12 This possibility is ruled out in the simulations by construction, because uncertainty affects the volatility of profits but not the expected productivity of capital. 13 Firms are asked the three following questions about financing problems: 1) "during the last year, did the firm desire to borrow more at the interest rate prevailing on the market?".…”
Section: Estimation Resultsmentioning
confidence: 99%
“…1 Second, direct examinations of risk preferences fail to detect significant differences in the expected direction between wage earners and the self-employed [e.g. Brockhaus (1980), Masters and Meier (1988), Miner and Raju (2004), Sarasvathy, Simon and Lave (1998)]. 2 A second candidate explanation is that some individuals are forced into selfemployment because unfavorable events limit wage-earning opportunities, while others are attracted into self-employment to pursue novel opportunities [see, for exam-1.…”
Section: Introductionmentioning
confidence: 99%